Electricity generation and in situ phosphate recovery from enhanced biological phosphorus removal sludge by electrodialysis membrane bioreactor. (January 2018) - Geng, Yi-Kun; Wang, Yunkun; Pan, Xin-Rong; Sheng, Guo-Ping
Graphical abstract: Highlights: An electrodialysis membrane bioreactor is used for energy and phosphorus recovery from EBPR sludge. Phosphorus in EBPR sludge can be released and concentrated to a relatively pure phosphate solution. Nitrogen is removed from EBPR sludge by desalination and denitrification processes. Abstract: In this study, a novel electrodialysis membrane bioreactor was used for EBPR sludge treatment for energy and phosphorus resource recovery simultaneously. After 30 days stable voltage outputting, the maximum power density reached 0.32 W/m 3 . Over 90% of phosphorus in EBPR sludge was released while about 50% of phosphorus was concentrated to 4 mmol/L as relatively pure phosphate solution. Nitrogen could be removed from EBPR sludge by desalination and denitrification processes. This study provides an optimized way treating sludge for energy production and in situ phosphorus recovery.